PHAGE TYPING OF COAGULASE POSITIVE STAPHYLOCOCCI - T. Zirakzadeh; F. Ghoreishi; V. Madjidi (Tehran University of Medical Sciences, 1976)
In determination of particular types of coagulate positive Staphylococci (Staphylococcus aurous) causing different diseases, especially hospital sepsis and food poisonings; 186 strains of coagulase positive Staphylococci from different provinces in Iran were phage typed. Because of various sources of the strains, the results had some differences, as 15.8 percent or 15 strains separated from children's hospital belonged to group I or the group causing hospital infections. These strains are an important factor in distribution of Staphylococci infections in hospitals and thus in society. From 18 strains separated from different kinds of foods, four strains or 22.2 per cent belonged to group IV, the group causing food poisoning. Therefore studying the epidemiology of Staphylococci infections should include phage typing of the strains, for separation of coagulase positive Staphylococci strains without phage typing can not have a scientific value, especially in the field of epidemiology.